SURGICAL EXPOSURE OF IMPACTED MAXILLARY CANINE AS AN ADJUNCT TO ORTHODONTIC TREATMENT: CASE REPORT - Sheoran, Kirtika; Pardeep, Singh; Gyanander, Attresh (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Disturbances in the eruption of permanent maxillary canines are common because they develop deep within the maxilla and have the longest path to travel compared with any other tooth in the oral cavity. The maxillary canine is second only to the mandibular third molars in frequency of impaction. The impacted canine has always implied a difficult therapeutical management for the clinician. The therapy of this condition can be considered successful only if the forced eruption and the subsequent alignment lead the tooth to a stable position in the dental arch along with the presence of a healthy periodontium